"Well, You Feel More Responsible When You're Unsupervised": Exploring Family Perspectives on Children's Independent Mobility - Negin A. Riazi; Mariana Brussoni; Patricia Vertinsky; Guy Faulkner (MDPI AG, 2021)
While children's independent mobility (CIM) is associated with various benefits, there is evidence of a generational decline in CIM in westernized countries; therefore, it is helpful to understand how CIM is currently negotiated between children and their parents. The purpose of this study was to examine children's and parents' perspectives and negotiations of CIM within the family unit. Face-to-face interviews and walk-along interviews were conducted with parents (n = 44) and children (n = 22), respectively. Interviews were audio-recorded and transcribed verbatim, and a thematic analysis was conducted. Four key preconditions were identified that facilitated negotiation of CIM within family units, including (1) the influence of parents' childhood experiences regarding their view of CIM (e.g., positive interpretations of childhood on parenting practices), (2) the role of children's individual characteristics on their independent mobility (e.g., child's confidence in their abilities), (3) family communication as a key coping strategy (parent-parent and parent-child communication), and (4) the influence of positive perceptions of the social environment on CIM. The findings suggest that CIM thrives when these conditions are present; as a result, it may be particularly helpful to develop policies and programs that support children's skill training, explore strategies to support communication between parents and children, and build neighbourhood connections.